1999
DOI: 10.1046/j.1365-2958.1999.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of yeast karyopherin Pse1p/Kap121p stimulates the mitochondrial import of hydrophobic proteins in vivo

Abstract: SummaryDuring evolution, cellular processes leading to the transfer of genetic information failed to send all the mitochondrial genes into the nuclear genome. Two mitochondrial genes are still exclusively located in the mitochondrial genome of all living organisms. They code for two highly hydrophobic proteins: the apocytochrome b and the subunit I of cytochrome oxidase. Assuming that the translocation machinery could not ef®ciently transport long hydrophobic fragments, we searched for multicopy suppressors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 52 publications
0
39
0
1
Order By: Relevance
“…Therefore, the steady-state levels of the ATP6 precursor and its ability to recognize the TOM complex in the outer mitochondrial membrane do not depend on the presence of the SOD2 39UTR. Notably, the relative proportions of ATP6 precursor and mature forms were analogous to the ones shown in cells for highly hydrophobic proteins en route to the mitochondria (Claros et al 1995;Corral-Debrinski et al 1999).…”
Section: Atp6-39utrmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, the steady-state levels of the ATP6 precursor and its ability to recognize the TOM complex in the outer mitochondrial membrane do not depend on the presence of the SOD2 39UTR. Notably, the relative proportions of ATP6 precursor and mature forms were analogous to the ones shown in cells for highly hydrophobic proteins en route to the mitochondria (Claros et al 1995;Corral-Debrinski et al 1999).…”
Section: Atp6-39utrmentioning
confidence: 55%
“…Mitochondrial sorting of mRNAs encoding mitochondrial proteins might likely represent a key step to ensuring the functionality of the corresponding polypeptides inside the organelle. In this case, a cotranslational phase might assist the import of the precursors (Corral-Debrinski et al 1999Fünfschilling and Rospert 1999;George et al 2002). We have demonstrated that in yeast, 47% of mRNAs encoding mitochondrial proteins are transported to the organelle surface (Sylvestre et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Third, yeast PSE1 may enhance secretion of proteins (9). Fourth, yeast PSE1 may augment mitochondrial import of hydrophobic mitochondrial proteins (12). It is, however, not clear whether these effects of karyopherin ␤3, PSE1, and/or KAP123 are direct or indirect ones.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of yeast overexpressing PSE1 led to the conclusion that karyopherin ␤3 may also play a role in mitochondrial protein import (12). It is tempting to speculate that NS5A binding to karyopherin ␤3 could prevent normal mitochondrial protein import, resulting in alterations of mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation